Regulatory phenotype, PD-1 and TLR3 expression in T cells and monocytes from HCV patients undergoing antiviral therapy: a randomized clinical trial. - Shan-shan Su; Huan He; Ling-bo Kong; Yu-guo Zhang; Su-xian Zhao; Rong-qi Wang; Huan-wei Zheng; Dian-xing Sun; Yue-min Nan; Jun Yu (PLoS ONE)
Background & aims The cellular immunity has a profound impact on the status of hepatitis C virus (HCV) infection. However, the response of cellular immunity on the virological response in patients with antiviral treatment remains largely unclear. We aimed to clarify the response of peripheral T cells and monocytes in chronic hepatitis C patients with antiviral treatment. Methods Patients with chronic hepatitis C were treated either with interferon alpha-2b plus ribavirin (n = 37) or with pegylated interferon alpha-2a plus ribavirin (n = 33) for up to 24 weeks. Frequencies of peripheral regulatory T-cells (Tregs), programmed death-1 (PD-1) expressing CD4+ T-cells or CD8+ T-cells and toll-like receptor (TLR) 3 expressing CD14+ monocytes were evaluated by flow cytometry in patients at baseline, 12 and 24 weeks following treatment and in 20 healthy controls. Results Frequencies of Tregs, PD-1 and TLR3 expressing cells were higher in patients than those in control subjects (P<0.05). Patients with complete early virological response (cEVR) showed lower Tregs, PD-1 expressing CD4+ or CD8+ T-cells than those without cEVR at 12 weeks (P<0.05). Patients with low TLR3 expressing CD14+ monocytes at baseline had a high rate of cEVR (P<0.05). Conclusions Low peripheral TLR3 expressing CD14+ monocytes at baseline could serve as a predictor for cEVR of antiviral therapy in chronic HCV-infected patients. The cEVR rates were significantly increased in the patients with reduced circulating Tregs, PD-1 expressing CD4+ or CD8+ T-cells. Trial registration Chinese Clinical Trial Registry ChiCTR10001090.